SGA children: auxological and metabolic outcomes – the role of GH treatment. (19th September 2013) - Saggese, Giuseppe; Fanos, Margherita; Simi, Francesca
Abstract: The definition Small for Gestational Age (SGA) describes those newborns weighing and/or measuring in length <−2 SD than expected for their gestational age. These subjects are at higher risk of short stature, neonatal complications, alterations of glucose, lipid metabolism, body composition, bone metabolism and puberty, neurocognitive vulnerabilities and alterations of the GH-IGF-I axis. With regards to growth, in 85–90% of the cases children born SGA experience a period of catch up growth that allows them to achieve an adult stature within normal range. In a 10–15% of the cases, the catch up growth period does not take place and this entails short stature in adulthood. In the latter group, GH treatment may be considered to achieve adult height in the range of genetical target stature. With reference to glucose and lipid metabolism, young adults born SGA and particularly those with early catch up growth are at higher risk of developing insulin resistance, type 2 diabetes mellitus, arterial hypertension, dyslipidemia, overweight, obesity and metabolic syndrome. Subjects born SGA are in need of a correct diagnostic and eventually therapeutic approach.